THE ROLE OF PKK IN COMMUNITY EMPOWERMENT IN TERUSAN TENGAH VILLAGE, TINGGI RAJA DISTRICT, ASAHAN REGENCY - Zerry Niana Puspa Sary; Syafruddin Ritonga; Walid Musthafa Sembiring (Pena Cendekia Insani, 2026)
This study aims to analyze the role of the Family Welfare Empowerment (PKK) organization in community empowerment in Terusan Tengah Village, Tinggi Raja District, Asahan Regency, and to identify the factors contributing to the lack of participation of the village PKK in district and provincial PKK competitions. This research employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the Village Head, the Chairperson of the PKK Team, the PKK Secretary, Working Group (Pokja) Chairpersons, and community members. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the role of PKK in community empowerment has been implemented through facilitative, educative, representative, and technical roles in accordance with Ife and Tesoriero’s role theory. PKK acts as a facilitator in mobilizing community participation, as an educator through counseling and skills training programs, as a representative in conveying community aspirations to the village government, and as a technical implementer in economic and family health empowerment programs. However, these roles have not been carried out optimally due to several constraints, including limited funding, low community participation, insufficient human resources, and inadequate external support. Therefore, it is necessary to strengthen cadre capacity, enhance government support, and develop more innovative strategies to increase community participation in order to optimize the role of PKK in community empowerment.